Strategy Research in Emerging Economies: Challenging the Conventional Wisdom* - Wright, Mike; Filatotchev, Igor; Hoskisson, Robert E.; Peng, Mike W. (Journal of Management Studies, 2005)
ABSTRACTThis review and introduction to the Special Issue on ‘Strategy Research in Emerging Economies’ considers the nature of theoretical contributions thus far on strategy in emerging economies. We classify the research through four strategic options: (1) firms from developed economies entering emerging economies; (2) domestic firms competing within emerging economies; (3) firms from emerging economies entering other emerging economies; and (4) firms from emerging economies entering developed economies. Among the four perspectives examined (institutional theory, transaction cost theory, resource‐based theory, and agency theory), the most dominant seems to be institutional theory. Most existing studies that make a contribution blend institutional theory with one of the other three perspectives, including seven out of the eight papers included in this Special Issue. We suggest a future research agenda based around the four strategies and four theoretical perspectives. Given the relative emphasis of research so far on the first and second strategic options, we believe that there is growing scope for research that addresses the third and fourth.